Pemanfaatan Ai Dalam Automated Market Intelligence (Ami) Untuk Pengambilan Keputusan Strategis Di Era Digital - Akbaruddin, Akbaruddin; Herdian, Yoga; Irawan, Debi; Ramadhan, Febriyansyah (CV. Green Publisher Indonesia, 2025)
In today's digital era, companies are expected to make decisions quickly and accurately in order to stay competitive in a rapidly changing market. One growing approach is the use of Artificial Intelligence (AI) in Automated Market Intelligence (AMI) systems. This study aims to explore how AI is applied in the process of automatically collecting and analyzing market data, and how it supports companies in developing business strategies. The research is based on a review of relevant literature and scientific publications, as well as analysis of case studies from companies that have implemented AI in their market intelligence processes. The findings show that AI can speed up data analysis, reduce decision-making errors, and provide more accurate market insights. This study is expected to serve as a useful reference for both business practitioners and researchers interested in understanding the role of AI in data-driven business strategies.